2023
DOI: 10.1039/d3ya00316g
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic modulation of thermoelectric transport properties of 2H-MoTe2

Tianhui Zhu,
Sree Sourav Das,
Safoura Nayeb Sadeghi
et al.

Abstract: Two-dimensional layered transition metal dichalcogenides are potential thermoelectric candidates with application in on-chip integrated nanoscale cooling and power generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In addition, various theoretical approaches have been utilized to assess the thermoelectric performance of 2D TMDCs [18][19][20][21][22]. Recent studies have also shown that the examination of the strain, anisotropy, and electrical modulation of 2D TMDCs can improve their transport performance [23][24][25][26][27][28]. However, currently there is no theoretical analysis that can accurately predict lattice thermal conductivity, in agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, various theoretical approaches have been utilized to assess the thermoelectric performance of 2D TMDCs [18][19][20][21][22]. Recent studies have also shown that the examination of the strain, anisotropy, and electrical modulation of 2D TMDCs can improve their transport performance [23][24][25][26][27][28]. However, currently there is no theoretical analysis that can accurately predict lattice thermal conductivity, in agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…This first-principles-based framework combining electron–phonon scattering and ionized impurity scattering has proven successful in previous studies of materials such as SnSe 2 , 73 MoSe 2 , 74 and MoTe 2 . 75 Through this approach, we aim to enhance the accuracy of our predictions and provide a more comprehensive understanding of the thermoelectric behavior of GeTe.…”
Section: Introductionmentioning
confidence: 99%